The Concept of Moral Education in the Qur'an; Study of the Interpretation of Surah Al-Hujurat Verse 11 - Hidayatullah; Iskandar Mirza (Kasyafa: Jurnal Pendidikan Agama Islam, 2025)
Moral education is one of the main pillars in Islamic teachings which aims to form individuals with noble character and create a harmonious social life. Morals not only serve as guidelines for individual behavior, but also become the main basis for maintaining healthy social relationships and their consequences. The Qur'an, as the holy book of Muslims, teaches many noble moral values. Surah Al-Hujurat verse 11 provides important guidelines in moral education, especially in three main aspects: humility, respect for others, and the importance of science. The relevance of Moral Education based on this verse is a). Personal Context: Teaches individuals to continue to improve themselves through faith, knowledge, and the practice of moral values. b). Social Context: Forming a harmonious society through mutual respect, tolerance and cooperation, c). Spiritual Context: Increasing awareness that morals and knowledge are a means of getting closer to Allah.